(x+2). (x+3). (x-4). (x-5) = 44 If a,b,c,d are the roots of the equations above then find the value of: a+b+c+d+ abcd
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yupp did the same way
Hey, Question is (x+2)(x+3)(x-4)(x-5)=44 not equal to 0
Log in to reply
I know, I just used the one that's equal to 0 because it shares some similarities with the one of the problem.
We take 44 on the LHS so the RHS=0.
As mention coefficient of x^3 remains the same and is equal to the sum of constants of each parenthesis..
Used the same logic.
absolutely right , i expected this type of solution only, i also used the same method to some extent .
Solve the equation and you get x 4 − 4 x 3 + 1 9 x 2 + 4 6 x + 7 6 .
Now by Vieta's Theorem Sum of Roots = 4 and Product of roots = 76.
Therefore 8 0
(x+2)(x+3)(x-4)(x-5)=44 when expanded, can be written as x^4-4x^3-19x^2+46x+76=0 sum of roots = -(-4)/1=4 product of roots = 76/1 (a+b+c+d)+abcd=4+76=80
nice solution , can be used though but if the question was edited and made a bit complex , then one would have to find value of all the roots then solve it.
Log in to reply
It depends on what is asked . For instance here it was directly asked something related to sum of roots and product of roots , so we could use this concept. Please also mention the method used by you to solve the same.
Problem Loading...
Note Loading...
Set Loading...
Let's analyze the equation ( x + 2 ) ( x + 3 ) ( x − 4 ) ( x − 5 ) = 0
The sum of its roots is the same as that of the equation of the problem, because subtracting 4 4 from the product doesn't change the coefficient of x 3 , which is equal to 2 + 3 − 4 − 5 = − 4 , giving a + b + c + d = 4
And the product of the roots of the equation above is 2 × 3 × 4 × 5 = 1 2 0 (I ignored the negative signs because there is an even amount of them). But a b c d = 1 2 0 − 4 4 = 7 6
So a + b + c + d + a b c d = 4 + 7 6 = 8 0